Given functions f(x) = 2x + 5 and g(x) = 4x + 1, find f(g(x)) for the following options: a) 2x + 6 b) 2x + 4 c) 6x + 4 d) 2x + 6

To find f(g(x)), we need to first calculate g(x) and then substitute it into the function f(x).

Given:

  • f(x) = 2x + 5
  • g(x) = 4x + 1

Let’s find g(x):

  • g(x) = 4x + 1

Now, we substitute g(x) into f:

  • f(g(x)) = f(4x + 1)
  • = 2(4x + 1) + 5
  • = 8x + 2 + 5
  • = 8x + 7

Now, we compare this result with the provided options:

  • a) 2x + 6
  • b) 2x + 4
  • c) 6x + 4
  • d) 2x + 6

None of the options match 8x + 7, which is our calculated result.

Thus, the correct expression for f(g(x)) is not listed among the given options.

More Related Questions